Risk of gastric cancer after bariatric surgery: a meta-analysis of retrospective studies - Li, Bing; Li, Xiaoxuan; Peng, Jihong; Zhang, Pengfei (Frontiers in Surgery, 2025)
ObjectivesAs obesity rates rise and Bariatric & Metabolic surgery (MBS) becomes more common, many patients with obesity opt for these procedures. Despite this, there are still concerns regarding the risk of postoperative gastric cancer. This study reviews comparative studies on the risk of gastric gancer among MBS vs. non MBS patients, reported in the last 15 years.Methods and study designWe conducted literature searches on PubMed, Web of Science, and Cochrane Library using specifically formulated terms and limited the publication period to 2000 to 2024. The number of people in the literature who underwent MBS and those who developed gastric cancer after MBS were extracted and statistically analyzed using RevMan 5.3. A random-effects model was employed to determine the merged odds ratio (OR) values, with the Mantel-Haenszel estimation method. Publication bias was assessed using a funnel plot. Heterogeneity between studies was analyzed with the Cochran Q (Chi-square) test and I² statistics.ResultsA total of nine studies reported the incidence of gastric cancer, with a total of 1,025,852 patients with obesity in the MBS group and 7,171,376 patients with obesity in the matched control group. After excluding the confounding factors commonly associated with gastric cancer in the included studies, we found that the incidence rate of gastric cancer was comparable for parents after MBS and patients with obesity (OR = 0.98, 95% CI 0.50–1.94, P = 0.96) in meta-analysis.ConclusionsIt appears that there is no significant difference in the risk of gastric cancer between patients with obesity who have undergone MBS and those who have not, further investigation is needed to define the long term risk. Consequently, concerns can be reduced in patients with obesity who are in urgent need of MBS but are worried about developing gastric cancer. It provides evidence-based medicine evidence for clinical treatment.